Pengaruh Berbagai Jenis Larutan Pengawet alami dan Lama Perendaman terhadap Kualitas Bunga Mawar Potong (Rosa hybrida L.) - Al Yamani, Putri Nabila Sukma; Hayati, Rita; Rahmawati, Marai (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 7 No 2 (2022)DO - 10.24843/JITPA.2022.v07.i02.p11, 2022)
Roses are flowers with high economic value but the freshness period is relatively short. The quality of cut roses can be maintained by treating the preservative solution with natural ingredients that are more practical and economical as well as long soaking. This study aims to determine the effect of various types of natural preservative solutions and immersion time on the quality of cut roses. This research was conducted at the Horticulture Laboratory, Department of Agrotechnology, Faculty of Agriculture, Syiah Kuala University, Darussalam Banda Aceh from December 2021 - January 2022. The factor studied was the type of natural preservative solution which consisted of 4 levels (control, 10% granulated sugar solution + 5% lemon extract, 40% young coconut water + 30% betel leaf boiled water and 10% sugar solution + 40% young coconut water + 30% betel leaf boiled water + lemon extract 5%) and immersion time consisting of 3 levels (2, 4 and 6 hours). The results showed that the type of natural preservative solution and the immersion time had a very significant effect (P<0,01) on the diameter of the bloom, the change in the cooling angle and the freshness of the cut roses. A solution of 10% granulated sugar + 40% young coconut water + 30% betel leaf boiled water + 5% lemon extract with 4 hours of immersion resulted in the largest flower diameter of 90mm with a freshness period of 8.33 days. Changes in the coolant angle can be maintained at 53.33° at 7 DAP with 10% granulated sugar + 5% lemon extract treatment with 2 hours of immersion.